REVIEW OF NATURAL CONVECTION HEAT TRANSFER FROM DIFFERENT CONFIGURATION OF HORIZONTAL RECTANGULAR FIN ARRAYS - Mr. Vishal Hegana; Mr.P.R. Kulkarni (International Journal of Innovations in Engineering Research and Technology, 2021)
Fin arrays on horizontal and vertical surfaces are used in variety of engineering applications to dissipate heat to the surroundings. Studies of heat transfer and fluid flow associated with such arrays are therefore of considerable engineering significance. The main controlling variables generally available to the designer are the orientation and the geometry of the fin arrays. In case of short horizontal arrays, it is observed that the air entering symmetrically from both the ends gets heated as it moves towards the Centre of the fin channel, as well as it rises due to decrease in density. So, the central portion of the fin becomes ineffective because hot air-stream passes over that part and therefore it does not bring about large heat transfer. The purpose of the present study is to investigate thoroughly the possibility of performance improvement of such arrays by providing a notch at the Centre and suggest for selection of optimum notch dimensions, and spacing by analyzing variety of fin Configuration.